Barriers and enablers to the emergence of distributed leadership in a Western Cape Government Health and Wellness district hospital - Motshweneng, Oupa Steven (Department of Public Health and Family Medicine, 2026)
Distributed leadership has been proposed to offer value for health systems – by enabling people to work towards collective goals within settings such as hospitals. Yet, there is still lack of clarity about what distributed leadership is and how to nurture its development. To address these knowledge gaps, this case study draws on conceptual work in empirically examining leadership in one district hospital in the Western Cape province, South Africa, seeking to identify evidence of distributed leadership and the factors influencing its emergence. Data were extracted from 28 academic theses, policies and strategic documents relating to health leadership, management and governance in the provincial health system (Phase 1) and 12 semi-structured, in-person interviews were conducted with hospital personnel (Phase 2). Phase 1 data provided the context of the case and guided the collection of data in Phase 2. All data were thematically analysed. The analysis reveals that there were pockets of distributed leadership within the hospital, as characterised by chains of multiple leaders working together to co-create shared meaning, take collective decisions and achieve common goals, enabled by relational leadership practices. These pockets supported both routine service delivery and bottom-up service improvement action. However, the unequal distribution of decision-making power, in the context of bureaucratic and professional hierarchies, limited the widespread emergence of distributed leadership. The case study suggests that distributed leadership can emerge in district hospitals with positive consequences for health service delivery, but that efforts to nurture its emergence should both bolster the leadership capabilities of individual leaders and address the bureaucratic and professional hierarchies that characterise the context within which hospital leadership unfolds. To aid the future practice of, and research about, distributed leadership the paper presents a comprehensive definition of the concept, synthesised from the wider literature and this study's empirical findings.